Clinical Characteristics and Outcome of Bleb-Related Infection in Glaucoma Patients - Sakaorat Petchyim; Subongkoch Subhadhirasakul; Darin Sakiyalak; Pichsaran Vessadapan; Ngamkae Ruangvaravate (Siriraj Medical Journal, 2022)
Objective: To study the clinical characteristics, causative organism, treatment, and clinical outcomes of bleb-related infection. Materials and Methods: The medical charts of patients who were diagnosed with bleb-related infection, including blebitis and bleb-related endophthalmitis (BRE), from September 2001 to December 2019 at Siriraj Hospital were reviewed. The patients’ demographic data, clinical characteristics, microorganisms found, treatment, and clinical outcomes were explored. Results: We found a total of 42 eyes from 41 patients had been diagnosed with blebitis (11 eyes) and BRE (31 eyes) over the 18-year study period. More than 80% of the patients had experienced pain and redness as the presenting symptoms. The most common bleb characteristic in BRE was purulent bleb (74.2%), while in blebitis it was bleb injection (45.5%). Bleb leakage was documented in 27.3% and 22.6% of patients with blebitis and BRE, respectively. Among the 41 patients, 10 had a history of minor trauma before the onset of infection, such as a rubbed eye, foreign body entering into the eye, water splashed into the eyes, or the eyes had been washed with soap. The yield of vitreous culture in bleb-related endophthalmitis was 48.3%. The most common microorganisms were Streptococcus spp., Enterococcus spp., and Haemophilus Influenzae. Generally, the treatment for blebitis at our institute is broad spectrum topical and systemic antibiotics, while intravitreal broad spectrum antibiotics are added to the treatment regimen for BRE patients. For BRE in our cohort, 11 eyes required vitrectomy and 7 eyes had undergone bleb excision. Treatment for blebitis tended to have a good visual outcome, with a stable visual prognosis for 9 out of the 11 eyes diagnosed with blebitis. However, most of the BRE eyes had a worsened visual outcome. Enterococcus spp. and Haemophilus Influenzae resulted in poor visual outcomes. Conclusion: The clinical characteristics of bleb-related infection in our patients were pain and redness. One fourth of patients had a history of minor trauma to the eye. To prevent bleb-related infection, the importance of patient education after trabeculectomy should be highlighted. Patients with presenting symptoms and unwanted behavior that could result in bleb infection should be identified and receive treatment alongside education.